EFFICACY AND SAFETY OF LINAC STEREOTACTIC RADIOSURGERY IN PATIENTS WITH SKULL-BASE MENINGIOMAS - Kruchok, Iryna; Чувашова, Ольга (The Ukrainian Scientific Medical Youth Journal, 2020)
Annotation. The article summarizes the arguments and counterarguments within the scientific discussion on the application of stereotactic radiosurgery in the treatment of patients with meningiomas of craniobasal localization. The main purpose of this study is to determine the effectiveness and safety of stereotactic radiosurgery in patients with meningiomas of craniobasal localization based on the assessment of local control parameters and probable post-radiation neurological deficit. Systematization of literature sources and approaches to solving the problem of treatment of patients with meningiomas of the skull showed that stereotactic radiosurgery can be used as a stand-alone method of treatment, and in addition to microsurgical removal of tumors. The relevance of this study is due to the limited possibilities of microsurgical removal of meningiomas of craniobasal localization, to achieve complete local control of tumors, as well as the high frequency of neurological deficits after surgery. Research methodology: retrospective analysis of the results of stereotactic radiosurgery 117 patients with 119 meningiomas of craniobasal localization treated from 2010 to 2014 in the State Institution "Institute of Neurosurgery named after AP Romodanov National Academy of Medical Sciences of Ukraine) on a linear accelerator Varian Trilogy, using data from clinical (Karnovsky Index) and neurological examination, magnetic resonance imaging before and after radiosurgery, volumetric study of local control during post-beam monitoring. The object of the study was selected patients with meningiomas of craniobasal localization. The article presents the results of the study: according to magnetic resonance imaging after 119 (100%) cases of meningioma of craniobasal localization with an average period of follow-up after treatment of 20.8 months in 96 (81%) cases tumor regression was determined; in 10 (11%) - there was a stabilization of the size of the tumor, which indicates the cessation of its growth. The increase in the proportion of patients with the Karnowski Index = 90 from 41.9% to 70.9%, indicates a high safety of the method. The study empirically confirms and theoretically proves that stereotactic radiosurgery is an effective and safe method of treatment of craniobasal meningiomas, which provides a high level of growth control (92%) while maintaining a high level of quality of life. The results of this study may be useful for creating an algorithm for the management of patients with meningiomas of the skull base